2014
DOI: 10.1007/s00595-014-0872-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic distal pancreatectomy: what factors are related to the learning curve?

Abstract: The length of the operation seems to be the main factor related to the CLC for laparoscopic distal pancreatectomy. The learning curve could be considered to be completed after about 17 procedures if performed by surgeons experienced with laparoscopic techniques at high-volume centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 13 publications
0
65
1
Order By: Relevance
“…Ricci et al [18] examined 32 cases involving laparoscopic distal pancreatectomy performed by a single surgeon (pancreatic surgeon), with the primary endpoint being operation time and the secondary endpoint being the conversion to laparotomy, rate of complication, mortality rate, postoperative hospital stay, and number of unscheduled splenectomies. The ROC curve is used as a statistical method to calculate the cut-off value for the learning curve, as was conducted in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Ricci et al [18] examined 32 cases involving laparoscopic distal pancreatectomy performed by a single surgeon (pancreatic surgeon), with the primary endpoint being operation time and the secondary endpoint being the conversion to laparotomy, rate of complication, mortality rate, postoperative hospital stay, and number of unscheduled splenectomies. The ROC curve is used as a statistical method to calculate the cut-off value for the learning curve, as was conducted in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, most pancreatic surgeons encounter complications after DP, especially postoperative pancreatic fistula (POPF). The incidence of POPF after DP has been reported to range from 18.6 to 64.9 % [2][3][4]. POPF causes a variety of postoperative complications, such as intra-abdominal abscess, delayed gastric emptying, and postoperative hemorrhage, due to pseudoaneurysm rupture.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar series of 55 patients undergoing robotic distal pancreatectomy, the inflection point for operative time occurred at 10 procedures; this was associated with an average operative time decreased from 421 to 249 minutes 26 . By comparison, Braga et al 27 reported operative time stabilized after 20 laparoscopic distal pancreatectomy procedures, and Ricci et al 28 reported that the laparoscopic distal pancreatectomy learning curve had been overcome by 17 procedures.…”
Section: Discussionmentioning
confidence: 99%